NEWS OF CONGRESS OF EUROPEAN SOCIETY OF CARDIOLOGY, VIENNA, SEPTEMBER 1-5, 2007 - S. Yu. Marcevich (Столичная издательская компания, 2015)
News of Congress of European society of cardiology, Vienna, September 1-5, 2007.